2018
DOI: 10.3389/fnagi.2018.00086
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Proliferating Olfactory Cells and Low Expression of Extracellular Matrix Genes Are Hallmarks of the Aged Olfactory Mucosa

Abstract: Background: The incidence of olfactory impairment increases with age; however, the detailed molecular and cellular mechanisms underlying this increase are yet to be determined.Methods: We examined the influence of aging on olfactory receptor neurons (ORNs), which are maintained by a unique stem cell system, from olfactory progenitor cells to mature ORNs, by histological comparisons of the physiological status of the olfactory epithelium between young adult and aged mice. Furthermore, we clarified the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 68 publications
0
34
0
Order By: Relevance
“…The characteristics of the response of aged OE to CSS may be attributed to the persistent inflammation of aged tissue. Generally, in aged populations, age-associated buildup of inflammatory cytokines (TNF, IL-1β and IL-6) within tissues is noted (Chaker et al, 2015 ; Ueha et al, 2018 ), and this elevation in inflammatory cytokines may result in a sustained state of chronic inflammation, known as the senescence-associated secretory phenotype, in aged populations. In the present study, the expression levels of Il1b and Il6 in the saline-treated aged mice were higher than those in the saline-treated young mice in the previous study (Ueha et al, 2016a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the response of aged OE to CSS may be attributed to the persistent inflammation of aged tissue. Generally, in aged populations, age-associated buildup of inflammatory cytokines (TNF, IL-1β and IL-6) within tissues is noted (Chaker et al, 2015 ; Ueha et al, 2018 ), and this elevation in inflammatory cytokines may result in a sustained state of chronic inflammation, known as the senescence-associated secretory phenotype, in aged populations. In the present study, the expression levels of Il1b and Il6 in the saline-treated aged mice were higher than those in the saline-treated young mice in the previous study (Ueha et al, 2016a ).…”
Section: Discussionmentioning
confidence: 99%
“…ORNs have regenerative potential through the olfactory epithelial stem-cell system (Bermingham-McDonogh and Reh, 2011 ). Olfactory dysfunction can occur due to a variety of causes, such as aging, exposure to toxic chemicals, airway allergy, upper-airway viral infections, head trauma and neurodegenerative diseases (Weiler and Farbman, 1997 ; Doty, 2009 ; Ueha et al, 2014 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although IGF-1 is mainly produced in the liver and skeletal muscles, it is also generated in the central nervous system, where it plays an important role in the differentiation and maturation of neurons ( Nishida et al, 2011 ; Nieto-Estevez et al, 2016 ; Pardo et al, 2016 ). As our previous study showed, reduction in ORN number and cell proliferation in the aged OE reduced gene expression of IGF-1, which may contribute to olfactory impairment during aging ( Ueha et al, 2018a ). Considering the previous studies, the balance of IGF-1 might be of importance in the regulation of OE homeostasis in the aging population.…”
Section: Introductionmentioning
confidence: 87%
“…Olfaction is known to be impaired by aging. Aging negatively affects the ORN cell system in the olfactory neuroepithelium (OE) ( Ueha et al, 2018a ). The OE has a unique regenerative stem-cell system, which is maintained by the life-long replenishment of mature ORNs in the luminal layer from the progenitor cells in the basal layer ( Costanzo, 1991 ; Schwob, 2002 ; Supplementary Figure S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The olfactory mucosa serves olfaction and consists of the olfactory epithelium (OE) and the sub-epithelium tissue. The number of mature olfactory receptor neurons (ORNs) in the OE is closely related to the degree of olfaction (Ueha et al, 2018a), and the ORNs are classified into four groups according to their zonal expression patterns (Mori et al, 2000). Regarding the impact of smoking on the OE, we previously reported that CS impaired the OE and olfaction by reducing the olfactory progenitor cells and mature ORNs (Ueha et al, 2016a) and that CS delayed regeneration of the OE (Ueha et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%